2019
DOI: 10.1007/s12192-019-01004-z
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and siRNA in combination reduces Hsp27 expression and induces caspase-3 activity in human glioblastoma cells

Abstract: GBM cells can easily gain resistance to conventional therapy, and therefore treatment of glioblastoma multiforme (GBM) is difficult. One of the hallmark proteins known to be responsible for this resistance is heat shock protein 27 (Hsp27) which has a key role in the cell survival. Resveratrol, a natural compound, exhibits antitumor effects against GBM, but there are no reports regarding its effect on Hsp27 expression in gliomas. The aim of the present study was to asses the effect of resveratrol on Hsp27 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Hsp27 is an important regulator of F-actin polymerization and it was shown that p38MAPK activation, followed by Hsp27 phosphorylation, was required for Phorbol 12-myristate 13-acetate (PMA)-induced migration of glioblastoma cells, suggesting that this chaperone is a potential target of negative chaperonotherapy to inhibit cancer invasion and progression [211]. This hypothesis was further supported by findings showing that Hsp27 downregulation synergizes the anticancer effects of different drugs and treatments, reducing GBM cell proliferation and promoting caspase 3-mediated apoptosis [212][213][214].…”
Section: Molecular Chaperones In Brain Tumorsmentioning
confidence: 99%
“…Hsp27 is an important regulator of F-actin polymerization and it was shown that p38MAPK activation, followed by Hsp27 phosphorylation, was required for Phorbol 12-myristate 13-acetate (PMA)-induced migration of glioblastoma cells, suggesting that this chaperone is a potential target of negative chaperonotherapy to inhibit cancer invasion and progression [211]. This hypothesis was further supported by findings showing that Hsp27 downregulation synergizes the anticancer effects of different drugs and treatments, reducing GBM cell proliferation and promoting caspase 3-mediated apoptosis [212][213][214].…”
Section: Molecular Chaperones In Brain Tumorsmentioning
confidence: 99%
“…Since GBM cells are resistant to anti-tumor drugs, the use of siRNA in combination with chemotherapy could be beneficial to enhancing the treatment efficiency [161]. For example, the combination of resveratrol (RES) and heat shock protein 27-knockdown using siRNA (Hsp27) was tested to treat the disease [162]. Hsp27 is a tumor-promoting factor in GBM implicated in ECM remodeling and cell survival.…”
Section: Innovative Treatments For Glioblastomamentioning
confidence: 99%
“…Heat shock proteins (HSPs) are involved in malignancy and HSP27 is one of these proteins. Overexpression of HSP27 causes metastasis of cancer cells via induction of epithelial–mesenchymal transition. , A combination of resveratrol and siRNA–HSP27 significantly inhibited the proliferation and migration of glioblastoma cells via down-regulation of HSP27 and activation of caspase-3, which, in turn, causes apoptosis of the cancer cells …”
Section: Natural Compounds–sirna Co-deliverymentioning
confidence: 99%
“…387,388 A combination of resveratrol and siRNA−HSP27 significantly inhibited the proliferation and migration of glioblastoma cells via down-regulation of HSP27 and activation of caspase-3, which, in turn, causes apoptosis of the cancer cells. 389 The use of nanoplatforms for co-delivery of Res and siRNA enhances their antitumor activity. Over the past decades, electrospun fibers have been considered ideal candidates for drug delivery because of their potential in acting as platforms for sustained drug release.…”
Section: ■ Introductionmentioning
confidence: 99%